THE DEVELOPMENT OF ENGLISH VOCABULARY RETENTION SKILLS THROUGH THE USE OF SONGS FOR GRADE 1 STUDENTS AT WATLADPLAKAO SCHOOL - Assavawongsanon, Variyakorn; Maneerat, Sukhon; Nimnuan, Patwalee (Journal of Interdisciplinary Development (Humanities and Social Sciences), 2026)
This research is a classroom action research study aimed at determining the effectiveness of a learning management plan using reading skill exercises to enhance the English vocabulary reading skills of first-grade students. It aims to compare students’ vocabulary reading skills before and after using the reading skill exercises and to examine students’ satisfaction with the exercises. The sample group consisted of first-grade students enrolled in a basic English course during the designated semester, selected through cluster random sampling. The research instruments included a learning management plan with reading skill exercises, a reading skill assessment test, and a student satisfaction questionnaire regarding the exercises. The statistical methods used for data analysis included percentage, mean, standard deviation, and a paired t-test (t-test Dependent) to compare students’ reading skills before and after the intervention. The results revealed that the learning management plan utilizing reading skill exercises to develop students’ English vocabulary reading skills met the predetermined effectiveness criteria. Students’ vocabulary reading skills significantly improved after the intervention at the .05 significance level, and their satisfaction with the exercises was at the highest level, with a mean score of 4.58.